Odpowiedź:
a)(a-6)²=a²-12a+36
b)(2x-3y)²=4x²-12xz+9y²
c)(2a+5)²-(2a-5)(2a+5)=4a²+20a+25-(4a²-25)=4a²+20a+25-4a²+25=20a+50
d)(√3-1)(√3+1)=3-1=2
e)(3√5-√10)²=45-6√50+10=55-30√2
f)(6+4x)(4x-6)=16x²-36
g)(2x+1)²-(2x-1)(1+2x)-(2x-5)²=
4x²+4x+1-(4x²-1)-(4x²-20x+25)=
4x²+4x+1-4x²+1-4x²+20x-25=
-4x²+24x-23
zad 2
[tex]\frac{\sqrt{33}}{\sqrt{3}}=\frac{\sqrt{33}*\sqrt{3}}{\sqrt{3}*\sqrt{3}}=\frac{\sqrt{99}}{3}[/tex]= [tex]\frac{3\sqrt{11}}{3}=\sqrt{11}[/tex]
zad 3
(√2+√5-√5-2)²=
(√2-2)²=2-4√2+4=6-4√2
Szczegółowe wyjaśnienie: